Integrins and cadherins join forces to form adhesive networks - Weber, Gregory F. (Company of Biologists, 2011)
Cell–cell and cell–extracellular-matrix (cell–ECM) adhesions have much in common, including shared cytoskeletal linkages, signaling molecules and adaptor proteins that serve to regulate multiple cellular functions. The term ‘adhesive crosstalk’ is widely used to indicate the presumed functional communication between distinct adhesive specializations in the cell. However, this distinction is largely a simplification on the basis of the non-overlapping subcellular distribution of molecules that are involved in adhesion and adhesion-dependent signaling at points of cell–cell and cell–substrate contact. The purpose of this Commentary is to highlight data that demonstrate the coordination and interdependence of cadherin and integrin adhesions. We describe the convergence of adhesive inputs on cell signaling pathways and cytoskeletal assemblies involved in regulating cell polarity, migration, proliferation and survival, differentiation and morphogenesis. Cell–cell and cell–ECM adhesions represent highly integrated networks of protein interactions that are crucial for tissue homeostasis and the responses of individual cells to their adhesive environments. We argue that the machinery of adhesion in multicellular tissues comprises an interdependent network of cell–cell and cell–ECM interactions and signaling responses, and not merely crosstalk between spatially and functionally distinct adhesive specializations within cells.